Sistem Layanan Legalisir Online Terintegrasi dengan Payment Gateway dan Jasa Ekspedisi - Permadi, Hermawan Budianto; Murtadho, Mohamad Ali; Wafa, Moh. Shohibul (Program Studi Teknik Informatika - Universitas Komputer Indonesia (UNIKOM), 2025)
Manual legalization of academic documents often leads to various issues such as long queues, slow processing times, and a lack of transparency in application status, especially for alumni who live far from campus. This makes it even more difficult for alumni due to transportation and accomodation issues. This study aims to design and develop an online legalization service system integrated with a payment gateway and delivery services to facilitate the legalization process for alumni. The system is developed using the Laravel framework and MySQL database, and integrates digital payment services via Midtrans and document delivery through Biteship as logistic aggregators. The result of this research is a web-based online legalization service system that allows alumni to submit legalization requests, make online payments, and choose document delivery options to their destination address. System testing shows that all features run well and can improve efficiency and user convenience in managing document legalization. Thus, this system can be a digital solution that supports faster, more transparent, and accessible academic administrative services.